The Naval Battle of Dhāt al-Ṣawārī (34/654-655) - Murat Öztürk; İsmail Koçuk (Şarkiyat Mecmuası)
Naval activities of the Muslim Arabs in the Middle East and central Mediterranean led to a famous sea battle with the Byzantine Empire, known as Dhāt al-Ṣawārī since the ships’ masts dominated the panorama. During the reign of Caliph ʿUthmān, the governors of Syria and Egypt, Muʿāwiya b. Abī Sufyān and ʿAbd Allāh b. Saʿd b. Abī Sarḥ, respectively, built a strong navy to protect the coastal cities and the newly conquered territories, and also to break the power of the Byzantium in the Mediterranean. ʿAbd Allāh b. Saʿd sailed from ʿAkkā to the northwest with the Egyptian and Shām fleets 200 ships strong. In response to the Muslim campaign, the Byzantine navy set sail under the personal command of Emperor Constans II (641-668). When the naval battle began on the coast of Finike (Phoenix) in Antalya, the Muslims tied the enemy ships to their own with ropes and chains and then started a hand-to-hand combat as if they were on land. When the battle was over towards noon, according to the sources, the sea was red with blood and the Emperor barely escaped from captivity under disguise. With the decisive victory of the Islamic Caliphate in 31 (652) or 34 (655), the Byzantine Empire not only lost its most valuable cities in the East, but also found a rival that was about to launch large-scale campaigns in the Mediterranean. This article examines Dhāt al-Ṣawārī (The Battle of the Masts) in light of the information from the main sources.